INFLUENCE OF ELECTRONIC WORD OF MOUTH (E-WOM) AND INFLUENCER CREDIBILITY ON PURCHASING DECISIONS AZARINE PRODUCT SKINCARE THAT INDICATE OVERCLAIMS (SURVEY ON FOLLOWERS OF THE TIKTOK @DOCTORDETECTIVE ACCOUNT) - Humairoh, Amanda; Sukardi, Yoki Oktorian (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2026)
The purpose of this study is to analyze the influence of influencer credibility and electronic word-of-mouth (E-WOM) on exaggerated claims made by consumers of Azarine skin care products, with a focus on followers of the TikTok account @DokterDetektif. The research method used is quantitative with a survey method. Data was collected through a questionnaire distributed to 100 respondents who are active TikTok users and have used Azarine products. The research results using SPSS Version 2.7 indicate that E-WOM has a positive and significant impact on Purchase Decisions, with a t-test value of approximately 3.886 (p < 0.001). Additionally, Influencer Credibility has a significant impact on Purchase Decisions with a t-test value of approximately 3.300 (p < 0.001). Furthermore, the F-test indicates that E-WOM and influencer credibility together have a significant impact on sales, with an F-test value of approximately 18.540 (p < 0.001). This study makes a significant contribution to understanding the digital landscape, particularly in the context of skin care products, and highlights the importance of transparency and credibility in influencing consumer behavior. It is hoped that the results of this study can serve as a guide for companies seeking to develop more effective marketing strategies Keywords: Electronic Word of Mouth, Influencer Credibility, Purchase Decision, Overclaim, Skincare.